Drawing meaning and direction from private native forest research – a summation of two recent studies. Issue 2 (3rd April 2019) - Cameron, N. L.; Lewis, T.; Ryan, S.
ABSTRACT: Information about the state and use of private native forests has been traditionally hard to gather, however, recent research in north-east New South Wales (NSW) and southern Queensland (QLD) is helping to bridge the knowledge gap. Research, recently completed by the NSW Department of Primary Industries and soon to be completed by the QLD Department of Agriculture and Fisheries, has used a combination of traditional and novel techniques to quantify the extent, status and value of private native forests and their role in domestic timber supply. The research supports the strategic planning priorities of NSW and QLD Governments.